Campus Party Brasil : o evento como meio de construção de um imaginário tribalista - Quadros, Taíla Lopes (2023)
Within the studies carried out in the dissertation, it was analyzed, considering the event as an object and the concept of tribes, what makes people feel like they belong to a tribe, to want to be part of communities, which can define and what identifies a group as a tribe and not just a gathering of people and how events can be responsible for creating an environment conducive to the creation of this feeling. We studied the question based on the analysis of the perception of some participants of the Campus Party Brasil event. An event related to technology that provides an immersive experience for its participants who have their own way of calling themselves, they are the campuseiros. As it is the object of the work, the concept and definition of events will be studied to contextualize the reason for this choice, in addition to presenting, for a better understanding, what the Campus Party Brasil event is and what its process and format is. The concepts of imaginary, characters and tribes are also studied to provide a basis for the investigated questions. The work uses a semi-structured interview as a methodology, leaving a space for the interviewees to present their experiences in an open way and allowing the addition of new questions or points to be discussed according to the progress of the dialogue. The people selected to participate in the interviews have different experiences and relationships with the event. The result of the interviews was analyzed from the perspective of comprehensive sociology worked by sociologist Michel Maffesoli. From the individual analysis of each interview and the crossing of insights, recurrent highlighted were observed where the triad of elements that are part of the construction of the tribe's imaginary in an event were identified, being space, presence and immersion.